Scientification of Politics or Politicization of Science: Reassessing the Limits of International Food Safety Lawmaking - Lin, Ching-fu (Science and Technology Law Review, 2013)
The proliferating food safety regulatory initiatives at domestic, international, and transnational levels by various actors with different perspectives have raised concerns for their important public health, international trade, and other implications. Standing as the hub of international food safety lawmaking, the Codex faces serious criticisms of its scientific soundness, legitimacy, transparency, and accountability. This paper explores the limits of Codex lawmaking structure and processes by examining whether its institutional design is adequate in terms of producing good governance. Food safety is an area of international law where political and cultural fragmentation collides with deep market integration and trade liberalization. Through a thorough analysis of the recent ractopamine dispute in the context of multilateral cooperation failure and the debates between technocracy and democracy models of legitimacy, this paper however emphasizes the forgotten role of procedural legitimacy in the current discourse, particularly mechanisms for avoiding conflicts of interest and fostering transparency.